Introduction to statistics and data analysis - Peck, Roxy (Singapore : Cengage Learning Asia Pte Ltd, 2019)
Traditional in structure but modern in spirit, the book incorporates material that reflects an increased emphasis on issues involved in data collection. This book features extensive treatment of probability with an emphasis on intuition and simulation rather than mathematical formalism-- Integrates the graphing calculator throughout the book
1. THE ROLE OF STATISTICS AND THE DATA ANALYSIS PROCESS -- 2. COLLECTING DATA SENSIBLY -- 3. GRAPHICAL METHODS FOR DESCRIBING DATA -- 4. NUMERICAL METHODS FOR DESCRIBING DATA -- 5. SUMMARIZING BIVARIATE DATA -- 6. PROBABILITY -- 7. RANDOM VARIABLES AND PROBABILITY DISTRIBUTIONS -- 8. SAMPLING VARIABILITY AND SAMPLING DISTRIBUTIONS -- 9. Estimation Using a Single Sample -- 10. HYPOTHESIS TESTING USING A SINGLE SAMPLE -- 11. COMPARING TWO POPULATIONS OR TREATMENTS --12. THE ANALYSIS OF CATEGORICAL DATA AND GOODNESS-OF-FIT TESTS -- 13. SIMPLE LINEAR REGRESSION AND CORRELATION: INFERENTIAL METHODS -- 14. MULTIPLE REGRESSION ANALYSIS -- 15. ANALYSIS OF VARIANCE: Single-Factor ANOVA and the F Test. -- 16. NONPARAMETRIC (DISTRIBUTION-FREE) STATISTICAL METHODS (ONLINE).
Includes index.
Keywords: MATHEMATICAL STATISTICS